Systematic review of evidence for relationships between physiological and CT indices of small airways and clinical outcomes in COPD. (June 2018) - Gove, Kerry; Wilkinson, Tom; Jack, Sandy; Ostridge, Kristoffer; Thompson, Bruce; Conway, Joy
Abstract: Background: Small airways disease (SAD) is considered pivotal in the pathology of COPD. There are numerous publications describing physiological and Computed Tomography (CT) imaging markers to detect SAD. However, there is no agreed gold standard and limited understanding of the clinical associations of these measures to disease outcomes. Methods: We conducted a systematic review using Embase, Medline and Pubmed to explore the relationship between physiological and CT SAD measures in COPD (GOLD Stages 1–4). Furthermore, evidence linking these physiological measures with defined clinical outcomes such as health status, functional assessment and exacerbation frequency were summarised. Results: The search yielded 1160 abstracts of which 21 met the search criteria. Eight studies examined physiological and CT measures while 13 publications identified physiological measures and clinical outcomes. Strong correlations were seen between CT and physiological measures of SAD. Varying associations between physiological measures and defined clinical outcomes were noted. Conclusions: Physiological and CT measures of SAD correlate and infer similar information. Physiological measures of SAD may offer valuable insight into clinical expression of the disease. A consensus on the standardisation and recommendation of tests to measure SAD is needed in order to better understand any clinical benefits of targeted drug therapy to the small airways. Highlights: CT and physiological indices of small airways disease have strong correlations. Associations between physiological indices and clinical outcomes are varied. There is a lack of standardisation of indices measuring small airways disease. Consensus and recommendations for the most appropriate indices are needed.